Problem Behaviors vs. the Situational Adversity Approach: HIV Risk Behaviors of Homeless Youth in Fort Lauderdale, Florida - Melanie J Simmons; Marlene LaLota (University of North Florida, 2005)
Problem behavior and situational adversity theories were used to investigate HIV risks among homeless youth. Problem behavior theory posits that youth with certain personality characteristics are more likely to engage in additional risk behaviors. Situational adversity warns against exposure to the social context of homelessness. We investigated the interaction between these concepts to explain two HIV-related risk behaviors: (1) non-condom use and (2) high-risk drug use among homeless youth (n=460) in Fort Lauderdale, Florida. An index of recurring problem behaviors represented that theory and two measures of homelessness represented situational adversity. Youth with both problem behaviors and homelessness experiences were the least likely to use condoms and the most likely to use high-risk drugs compared to youth with only problem behaviors, youth with homelessness experiences only or youth with neither. One finding contradicted the situational adversity hypothesis, and in the absence of problem behaviors, duration homelessness was not related to high-risk drug use.